The Microbiota–Gut–Brain Axis–Heart Shunt Part II: Prosaic Foods and the Brain–Heart Connection in Alzheimer Disease - Mark Obrenovich; Shams Tabrez; Bushra Siddiqui; Benjamin McCloskey; George Perry (Microorganisms, 2020)
There is a strong cerebrovascular component to brain aging, Alzheimer disease, and vascular dementia. Foods, common drugs, and the polyphenolic compounds contained in wine modulate health both directly and through the gut microbiota. This observation and novel findings centered on nutrition, biochemistry, and metabolism, as well as the newer insights we gain into the microbiota-gut-brain axis, now lead us to propose a shunt to this classic triad, which involves the heart and cerebrovascular systems. The French paradox and prosaic foods, as they relate to the microbiota-gut-brain axis and neurodegenerative diseases, are discussed in this manuscript, which is the second part of a two-part series of concept papers addressing the notion that the microbiota and host liver metabolism all play roles in brain and heart health.